Priming the Comprehension of German Object Relative Clauses. Issue 3 (3rd July 2017) - Brandt, Silke; Nitschke, Sanjo; Kidd, Evan
ABSTRACT: Structural priming is a useful laboratory-based technique for investigating how children respond to temporary changes in the distribution of structures in their input. In the current study we investigated whether increasing the number of object relative clauses (RCs) in German-speaking children's input changes their processing preferences for ambiguous RCs. Fifty-one 6-year-olds and 54 9-year-olds participated in a priming task that (i) gauged their baseline interpretations for ambiguous RC structures, (ii) primed an object-RC interpretation of ambiguous RCs, and (iii) determined whether priming persevered beyond immediate prime-target pairs. The 6-year old children showed no priming effect, whereas the 9-year-old group showed robust priming that was long lasting. Unlike in studies of priming in production, priming did not increase in magnitude when there was lexical overlap between prime and target. Overall, the results suggest that increased exposure to object RCs facilitates children's interpretation of this otherwise infrequent structure, but only in older children. The implications for acquisition theory are discussed.